안정한 DLC 코팅에 의한 블레이드 옆면 마찰계수 감소가 다이아몬드마이크로 블레이드의 절삭성능과 내구성에 미치는 영향 - 장재철; Jae Cheol Jang; 김송희; Song Hee Kim (대한금속·재료학회지, 53(9), 2015)
A DLC coating was deposited onto diamond micro-blades with Cu/Sn bond metal doped with WS2 and MoS2 as a solid lubricant to enhance the cutting efficiency. In comparison with blades without the DLC coating, the blades with the DLC coating showed a decreased specific wear rate in a ball-on-disc wear test and less momentary energy consumption in a dicing test. This is ascribed to reduction of the lateral friction coefficient with the work piece. A qualitative analysis of the reduction of momentary energy consumption was carried out to evaluate the effect of DLC coating on dicing performance. Chipping sizes of the diced workpiece surfaces were reduced by the DLC coating, which is beneficial for accurate machining.